2003
DOI: 10.1046/j.1439-0434.2003.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Fusarium and Verticillium Wilt of Tomato by Penicillium oxalicum under Greenhouse and Field Conditions

Abstract: Treatments with conidia of Penicillium oxalicum produced in a solid‐state fermentation system were applied at similar densities (6 × 106 spores/g seedbed substrate) to tomato seedbeds in water suspensions (T1: 5 days before sowing, or T2: 7 days before transplanting; 15 days after sowing), or in mixture with the production substrate (T3: 7 days before transplanting; 15 days after sowing). Treatments T2 and T3 significantly (P = 0.05) reduced fusarium wilt of tomato in both greenhouse (artificial inoculation) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…On the basis of morphology and the ITS sequence, strain PY-1 was identified as Penicillium oxalicum. As a biological control agent, P. oxalicum could suppress several plant diseases, for example Phytophthora root rot of azalea (Gintis and Benson 1987), Pythium seed rot and pre-emergence damping-off of chickpea (TraperoCasas et al 1990), and tomato Fusarium wilt and Verticillium wilt (De Cal et al 1995, 1999Larena et al 2003;Sabuquillo et al 2005). Evidence suggested that the biocontrol mechanism of P. oxalicum is mainly because of induced resistance of the plant (De Cal et al 2000); Pectinases from P. oxalicum could induce resistance in cucumber against Cladosporium cucumerinum (Peng et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of morphology and the ITS sequence, strain PY-1 was identified as Penicillium oxalicum. As a biological control agent, P. oxalicum could suppress several plant diseases, for example Phytophthora root rot of azalea (Gintis and Benson 1987), Pythium seed rot and pre-emergence damping-off of chickpea (TraperoCasas et al 1990), and tomato Fusarium wilt and Verticillium wilt (De Cal et al 1995, 1999Larena et al 2003;Sabuquillo et al 2005). Evidence suggested that the biocontrol mechanism of P. oxalicum is mainly because of induced resistance of the plant (De Cal et al 2000); Pectinases from P. oxalicum could induce resistance in cucumber against Cladosporium cucumerinum (Peng et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using Penicillium oxalicum and non-pathogenic F. oxysporum (e.g. Duijff et al 1998;Larena et al 2003;Shishido et al 2005), have demonstrated significant reductions in the incidence and severity of tomato Fusarium wilt disease. Plant growth promoting fungi (PGPF) have also been reported to suppress plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…to totally suppress Verticillium wilt of potato when incorporated into the culture substrate 15 days before pathogen challenge. In the same way, Larena et al [53] have successfully suppressed tomato vascular wilts caused by V. dahliae and F. oxysporum f. sp. lycopersici both under growth chamber and field conditions using P. oxalicum based treatments.…”
Section: Discussionmentioning
confidence: 88%